Determination of optimum aging time for cuvee of rose sparkling wine - Скорченко, Марія Вікторівна; Білько, Марина Володимирівна (Eastern-European Journal of Enterprise Technologies, 2015)
To assess the aging effect on the pink sparkling wine quality, mass concentrations of phenolic and coloring substances, optical and redox properties of the cuvee of Pinot Noir, Chardonnay and Cabernet Sauvignon were analyzed. It was shown that the mass concentrations of anthocyanins and phenolic substances have reached their minima in the 10th and 11th months of aging, respectively. In addition, the optical characteristics had the best value until the 10th month. The value of the redox characteristics also varied in the process of aging. Steady growth of Eh0 during the period from 0 to 10 months is most likely caused by the appearance of unoxidized autolysis products in the system. However, this figure began to decline in the 11th-12th month of aging that indicates the beginning of oxidation. The research results have shown that the aging time of pink sparkling wine should be consistent with a number of characteristics. It was recommended to hold aging of pink blended cuvee no longer than 10‑11 months.